ISSUES OF DEVELOPING UZBEKISTAN'S COOPERATION WITH REGIONAL ORGANIZATIONS AND FOREIGN STATES IN THE SPHERE OF MIGRATION - Kamilov Oybek (Scholar Express Journals, 2025)
This article examines the issues of developing Uzbekistan's cooperation with regional organizations and foreign states in the sphere of migration. The article analyzes Uzbekistan's current position in the migration sphere and explores areas of cooperation with regional organizations such as the Commonwealth of Independent States, Shanghai Cooperation Organization, European Union, Eurasian Economic Union, as well as with foreign countries. As a result of the research, proposals aimed at developing Uzbekistan's migration diplomacy and addressing practical issues in this field are put forward. The article concludes with recommendations for improving the legal framework of regional and bilateral cooperation on migration regulation.
Keywords: migration policy; regional cooperation; international organizations